IN-HOME-PDCaregivers: The effects of a combined home visit and peer mentoring intervention for caregivers of homebound individuals with advanced Parkinson's disease. (January 2023) - Fleisher, Jori E.; Suresh, Madhuvanthi; Klostermann, Ellen C.; Lee, Jeanette; Hess, Serena P.; Myrick, Erica; Mitchem, Daniela; Woo, Katheryn; Sennott, Brianna J.; Witek, Natalie P.; Chen, Sarah Mitchell; Beck, James C.; et al.
Abstract: Introduction: Family caregivers of people with advanced Parkinson's Disease (PD) are at high risk of caregiver strain, which independently predicts adverse patient outcomes. We tested the effects of one year of interdisciplinary, telehealth-enhanced home visits (IN-HOME-PD) with 16 weeks of peer mentoring on caregiver strain compared with usual care. Methods: We enrolled homebound people with advanced PD (PWPD) and their primary caregiver as IN-HOME-PD dyads. We trained experienced PD family caregivers as peer mentors. Dyads received four structured home visits focused on advanced symptom management, home safety, medications, and psychosocial needs. Starting at approximately four months, caregivers spoke weekly with a peer mentor for 16 weeks. We compared one-year change in caregiver strain (MCSI, range 0–72) with historical controls, analyzed intervention acceptability, and measured change in anxiety, depression, and self-efficacy. Results: Longitudinally, IN-HOME-PD caregiver strain was unchanged (n = 51, 23.34 (SD 9.43) vs. 24.32 (9.72), p = 0.51) while that of controls worsened slightly (n = 154, 16.45 (10.33) vs. 17.97 (10.88), p = 0.01). Retention in peer mentoring was 88.2%. Both mentors and mentees rated 100% of mentoring calls useful, with mean satisfaction of 91/100 and 90/100, respectively. There were no clinically significant improvements in anxiety, depression, or self-efficacy. Conclusions: Interdisciplinary telehealth-enhanced home visits combined with peer mentoring mitigated the worsening strain observed in caregivers of less advanced individuals. Mentoring was met with high satisfaction. Future caregiver-led peer mentoring interventions are warranted given the growing, unmet needs of PD family caregivers. Trial registration: NCT03189459 Highlights: Family caregivers of those with advanced Parkinson's Disease experience high strain. Home visits and peer mentoring in Parkinson's caregivers mitigated worsening strain. Caregiver peer mentoring had high retention, fidelity, utility, and satisfaction.